2012
DOI: 10.5194/acp-12-3165-2012
|View full text |Cite
|
Sign up to set email alerts
|

Particle mass yield from <i>β</i>-caryophyllene ozonolysis

Abstract: Abstract. The influence of second-generation products on the particle mass yield of β-caryophyllene ozonolysis was systematically tested and quantified. The approach was to vary the relative concentrations of first- and second-generation products by adjusting the concentration of ozone while observing changes in particle mass yield. For all wall-loss corrected organic particle mass concentrations Morg of this study (0.5 < Morg < 230 μg m−3), the data show that the particle-phase organic material was comp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
52
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(69 citation statements)
references
References 66 publications
14
52
3
Order By: Relevance
“…The aerosol density was found to be insensitive to a range of other experimental parameters, including starting α-phellandrene and ozone concentrations, aerosol loading, aerosol oxidation state and the presence of CI scavengers. These findings are in contrast to studies conducted on α-pinene (Shilling et al, 2009) and β-caryophyllene (Chen et al, 2012), in which particle density was found to decrease as chamber aerosol loadings Figure 11. Impact of sCI scavengers on particle nucleation shown by (a) peak particle number distributions scaled for the amount of α-phellandrene reacted in all experiments and (b) particle number distributions evolution over the first hour of experiments 1 and 6.…”
Section: Soa Formationcontrasting
confidence: 55%
“…The aerosol density was found to be insensitive to a range of other experimental parameters, including starting α-phellandrene and ozone concentrations, aerosol loading, aerosol oxidation state and the presence of CI scavengers. These findings are in contrast to studies conducted on α-pinene (Shilling et al, 2009) and β-caryophyllene (Chen et al, 2012), in which particle density was found to decrease as chamber aerosol loadings Figure 11. Impact of sCI scavengers on particle nucleation shown by (a) peak particle number distributions scaled for the amount of α-phellandrene reacted in all experiments and (b) particle number distributions evolution over the first hour of experiments 1 and 6.…”
Section: Soa Formationcontrasting
confidence: 55%
“…This suggests that the magnitude of losses of vapors to the walls for this fastreacting system is of the same order as the variability of the yields calculated in the rest of the experiments, with artifacts of the order of 20-30 %. The average density of the SOA formed in the ozonolysis experiments was 0.99 ± 0.05 µg m −3 (Table 1), a value lower than the values calculated by Chen et al (2012). The approaches that were used for the density estimation are different; we matched the full distributions, while Chen et al (2012) relied on the mass mode diameters.…”
Section: Ozonolysismentioning
confidence: 92%
“…Winterhalter et al (2009) Lee et al (2006a, b), Alfarra et al (2012) and Hoffmann et al (1997) calculated the SOA assuming an effective density ranging from 1 to 1.3 µg m −3 , depending on the study. Chen et al (2012) estimated effective density values from 1.23 to 1.81 µg m −3 for their experiments. Relative humidity and temperature might also affect the yield.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…β-caryophyllene was the main sesquiterpene in many emission studies in boreal forests Tarvainen et al, 2005), but it has never been detected in the ambient air, due its high reactivity. β-caryophyllene could be a major source of SOA, due to its reactivity and high aerosol yields in smog chamber studies (Jaoui et al, 2003;Lee et al, 2006;Chen et al, 2012).…”
Section: Introductionmentioning
confidence: 99%